Tinjauan Yuridis New Novelty Dalam Pengajuan Permohonan Hak Paten - Ramadhan Fajar Prasetyo; Waluyo Waluyo (Universitas 45 Surabaya, 2023)
Regarding the research of this thesis, the author in his research uses the normative juridical method, which means that the research refers to legal norms in national laws. This study also aims to determine the application of the new novelty principle in filing a patent application and to find out the legal consequences for patent applicants who do not use the new novelty principle. The source of this research data is obtained from the data collection in this research is done by studying documents or literature. Document or literature study is the main data collection technique because the proof of the basic assumptions of research is based on positive legal norms, legal doctrines or teachings, academic research results and court decisions, all of which are based on written documents. Related to document study, basically it is an activity of reviewing various written information regarding the law, whether it has been published or not published in general but may be known by certain parties. Document study is the activity of collecting and examining and tracing documents or literature that can provide information or information needed by researchers. The results of the study indicate that the principle of new and novelty is an absolute requirement in patent registration in accordance with Law Number 13 of 2016.